2008
DOI: 10.1161/strokeaha.107.491779
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Incidence and Survival in the Beginning of the 21st Century in Southern Sweden

Abstract: Background and Purpose— We report trends of stroke incidence and survival up to year 2001/2002 in Lund-Orup, Sweden, and projections of future stroke incidence in Sweden. Methods— Lund Stroke Register, a prospective population-based study, included all first-ever stroke patients, between March 1, 2001 and February 28, 2002, in the Lund-Orup health care district. Institution-based studies for 1983 to 1985 and 1993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 45 publications
9
88
1
3
Order By: Relevance
“…Rates may also change due to change in reporting, better diagnoses, as well as improvements of assistive devices. For example, the increased prevalence of mild stroke between 1992 and 2002 could be due to the combined effect of stable incidence rates and increased survival after stroke reported in other Swedish studies (Hallstrom et al 2008;Stegmayr and Asplund 2003). In addition, as a consequence of increased knowledge among patients and physicians mild strokes may have been increasingly detected and diagnosed (Stegmayr and Asplund 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Rates may also change due to change in reporting, better diagnoses, as well as improvements of assistive devices. For example, the increased prevalence of mild stroke between 1992 and 2002 could be due to the combined effect of stable incidence rates and increased survival after stroke reported in other Swedish studies (Hallstrom et al 2008;Stegmayr and Asplund 2003). In addition, as a consequence of increased knowledge among patients and physicians mild strokes may have been increasingly detected and diagnosed (Stegmayr and Asplund 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Exclusion of 2 studies 12,14 which did not report 1-month outcomes, and 1 study with an exceptionally low case-fatality rate of 8%, 39 did not substantially alter the results. Eighteen studies including our own 11,13,[21][22][23][24][25][27][28][29][31][32][33]35,37,38 reported the mean age of cases with SAH and proportion of women. After adjustment for age and sex, there was a similar but nonsignificant reduction in case-fatality of 0.9% per annum (Ϫ0.2 to 2.0%, p ϭ 0.10).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The resulting co-morbidity probably contributes to higher case fatality rates and we hypothesise that death could be reduced by improved active rehabilitation following stroke. 3 Indeed, studies of stroke survivors in the UK, Japan and Hungary have noted the link between survival and active poststroke medical management. 21,22 While other authors have noted most of these variables as predictive of post-stroke outcome, it is those factors which were not associated with case fatality which are perhaps the most interesting.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In low-and middle-income regions, the situation is more complex. With limited provision of primary healthcare in many regions, poststroke mortality rates remain high, and demographic changes mean that as populations age, rates of stroke-attributable mortality are likely to continue to rise.…”
mentioning
confidence: 99%